Oops! Sorry that is not correct. You almost got it but
it should be 49y² - 1
:)
Remember to multiply the variables too. :)
A Lil Tip:
When multiplying two binomials, you may try to use the FOIL method.
FOIL stands for
F- first terms
O - outer terms
I - inner terms
L - last terms
:)
2006-09-10 06:42:39
·
answer #1
·
answered by ←deadstar→ 3
·
0⤊
0⤋
Its:
49y^2-1
2006-09-10 06:39:45
·
answer #2
·
answered by smartypantsleen 3
·
0⤊
0⤋
You've mastered the concept, but you forgot to show that you multiplied 7y by 7y. So if you turned this in at school, you'd not earn all the points...
7y*7y=49y^2
+7y-7y=0
-1*+1=-1
the correct answer is 49y^2 -1
(7y-1)(7y+1)
49y^2+7y-7y-1
49y^2-1
Good work, you understand the concept, you just made a small error. Good luck in your mastery of math!
2006-09-10 07:35:31
·
answer #3
·
answered by ronw 4
·
0⤊
0⤋
Hi
See u have got the the equation which looks like (a+b)(a-b), which equals to a^2 - b^2
So, the simplification of your equation will be,
(7y)^2 - 1^2 = 49y^2-1
2006-09-10 06:42:17
·
answer #4
·
answered by M1976 2
·
0⤊
0⤋
it should be 49y^2 - 1 (the y should be squared)
you could skip the middle step if u use the formula
(a+b) (a-b) = a^2 - b^2
2006-09-10 06:37:25
·
answer #5
·
answered by Rollester 4
·
1⤊
0⤋
You are almost right, the y has to be squared: 49y^2-1.
2006-09-10 06:35:33
·
answer #6
·
answered by bruinfan 7
·
1⤊
1⤋
4y+3x=7 -3x -3x 4y=-3x+7 /4 /4 y=(3/4)x+(4/7) 2x+7y=4 -2x -2x 7y=-2x+4 /7 /7 y= -(2/7)x+(4/7) c=d/g *d *(times)d cd=g ax+by=c -ax -ax by= -ax+c /b /b y=(-ax/b)+(c/b) m/n=p/q *q *q (m/n)q = p Yeah, I've had bad math teachers before. You just get the variable you're solving for alone by using opposite operations. Good luck! P.S. The ones in parenthesis should be written as fractions.
2016-03-27 05:30:55
·
answer #7
·
answered by ? 4
·
0⤊
0⤋
14
2006-09-10 06:57:01
·
answer #8
·
answered by NY Lady 5
·
0⤊
1⤋
your answer is correct but the correct method is different
look
its easy
there is and lagebriac formula: (a+b) (a-b) = a2-b2 (a raise to the power 2 - b raise to the power 2)
here
a = 7y and
b = 1
the answer is like (according to formula)
(7y+1) (7y-1) = 49y2-1 (((49)x(y raise to the power 2)) -1)
2006-09-10 06:38:42
·
answer #9
·
answered by shahidrock 3
·
0⤊
0⤋
almost it's 49y square minus 1
lol
2006-09-10 07:08:57
·
answer #10
·
answered by watchamakalit_beibe 3
·
0⤊
0⤋